Continually recruited naïve T cells contribute to the follicular helper and regulatory T cell pools in germinal centers - Julia Merkenschlager; Riza-Maria Berz; Victor Ramos; Maximilian Uhlig; Andrew J. MacLean; Carla R. Nowosad; Thiago Y. Oliveira; Michel C. Nussenzweig (Nature Communications, 2023)
Abstract Follicular helper T cells (TFH) mediate B cell selection and clonal expansion in germinal centers (GCs), and follicular regulatory T cells (TFR) prevent the emergence of self-reactive B cells and help to extinguish the reaction. Here we show that GC reactions continually recruit T cells from both the naïve conventional and naive thymic regulatory T cell (Treg) repertoires. In the early GC, newly recruited T cells develop into TFH, whereas cells entering during the contraction phase develop into TFR cells that contribute to GC dissolution. The TFR fate decision is associated with decreased antigen availability and is modulated by slow antigen delivery or mRNA vaccination. Thus, invasion of ongoing GCs by newly developing TFH and TFR helps remodel the GC based on antigen availability.